Identificação de peptídeos intracelulares em cérebro de camundongos submetidos à privação e restrição de sono - Polster, Gabriela [UNIFESP] (2016)
Neuropeptides have a fundamental role in the functioning of the whole organism and in particular in the central nervous system. The activity of a number of neuropeptides, especially interaction with their receptors has been widely studied. However, recently, intracellular peptides with biological activity have been found in several models. The identification and generation mechanisms of these assets intracellular peptides from inactive or active precursors and the mechanisms of action of these compounds has been less detailed in the literature. Our interest then turned to the identification and quantification of intracellular peptides in the brains of mice C57 / Bl6 controls or subjected to different sleep deprivation protocols. In our study we identified intracellular peptides and neuropeptides with special attention to the MAKVALIVILLFVL peptide, Melanopsin receptor fragment, which had not been identified in previous peptidomics studies